Mesomelia‐synostoses syndrome: Description of a patient presenting a monoallelic expression of SULF1 without alterations in the SLCOA1 gene. Issue 2 (18th November 2018) - Dardis, Andrea; Pianta, Annalisa; Zampieri, Stefania; Zanin, Irene; Bertoli, Marta; Cazzagon, Monica; Bregant, Elisa; Damante, Giuseppe; Bembi, Bruno; Ciana, Giovanni
Abstract :